KETERGANTUNGAN MAHASISWA TERHADAP PENGGUNAAN KECERDASAN BUATAN DALAM PENYELESAIAN TUGAS AKADEMIK DI ERA DIGITAL - Egi Bayu Setiawan; Muhammad Adrian; Isa Faqihuddin Hanif (CV. Denasya Smart Publisher, 2026)
The rapid development of artificial intelligence (AI) has significantly influenced higher education, particularly in supporting students’ academic activities. This study aims to analyze the level of student dependence on AI in completing academic assignments and its implications for critical and creative thinking skills. A quantitative descriptive approach was employed by distributing questionnaires to 20 undergraduate students from various universities and academic disciplines. The results indicate that AI is widely perceived as helpful and time-efficient; however, excessive reliance may reduce students’ independence in problem-solving and analytical thinking. These findings highlight the importance of balanced and responsible AI utilization to ensure that technological assistance does not hinder students’ intellectual development.